Proceedings: Immune Tolerance and Stem Cell Transplantation: A CIRM Mini-Symposium and Workshop Report. (3rd December 2014) - Talib, Sohel; Millan, Maria T.; Jorgenson, Rebecca L.; Shepard, Kelly A.
Abstract : In July 2014, the California Institute for Regenerative Medicine held a workshop to consider strategies for overcoming immune rejection in patients receiving stem cell treatments. A Roadmap to Tolerance was developed, identifying four fundamental steps for advancing strategies to prevent graft rejection and induce tolerance to stem cell-based tissues. Abstract: The mission of the California Institute for Regenerative Medicine (CIRM) is to accelerate stem cell treatments to patients with unmet medical needs. Immune rejection is one hurdle that stem cell therapies must overcome to achieve a durable and effective therapeutic benefit. In July 2014, CIRM convened a group of clinical investigators developing stem cell therapeutics, immunologists, and transplantation biologists to consider strategies to address this challenge. Workshop participants discussed current approaches for countering immune rejection in the context of organ transplant and cellular therapy and defined the risks, challenges, and opportunities for adapting them to the development of stem cell-based therapeutics. This effort led to the development of a Roadmap to Tolerance for allogeneic stem cell therapy, with four fundamental steps: (a) the need to identify "tolerance-permissive" immune-suppressive regimens to enable the eventual transition from current, drug-based approaches to a newer generation of technologies for inducing tolerance; (b) testing new biologics and small molecules for inducing tolerance in stem cell-based preclinical and clinical studies; (c) stimulation of efforts to develop novel therapeutic approaches to induce central and peripheral tolerance, including manipulation of the thymus, transplantation of purified stem cells, and cell therapy with T-regulatory cells; and (d) development of robust and sensitive immune monitoring technologies for identifying biomarkers of tolerance and rejection after allogeneic stem cell treatments in the clinical setting.